Nutritional assistance and gestational diabetes mellitus: an integrative literature review (Research, Society and Development, 2020)
Gestational diabetes mellitus (GDM) is one of the most frequent metabolic complications of pregnancy, which is triggered as intolerance to carbohydrates of varying severity and may persist or not after delivery. Nutritional therapy is important in all stages of life, especially during pregnancy, since this cycle is guided by physiological changes that require quality and humanized prenatal and puerperal care. Thus, the objective was to carry out an integrative literature review on the theme “Nutritional assistance related to complications resulting from pregnancies aggravated by DMG. The methodology was based on the analysis of literary works, clinical guidelines as well as magazines and online articles taken from SCIELO and PUBMED, in Portuguese that dealt with the theme, and published between the years 2015-2020, whose search was made using the descriptors: gestational diabetes, risk factors and nutritional therapy. 16 articles were identified, of which only 10 met the criteria. According to the findings in the studies, it is clear that the appreciation of comprehensive care for pregnant women at risk or established diagnosis of gestational diabetes is necessary in order to reduce or avoid complications resulting from this clinical condition, therefore it is essential to have the care of a multiprofessional team, especially the nutritionist, as nutritional monitoring in pregnancy complicated by DMG contributes to glycemic control, adequate weight and avoids greater risks for the mother and fetus during and after pregnancy.